The Relationship Between Breastfeeding and The Incidence of Stunting in The Tanrutedong Community Health Center Working Area, Sidrap Regency - Rahimah, Nur; Arfah, Arni Isnaini; Darussalam, Andi Husni Esa; Jafar, Muhammad Alfian; Pramono, Sigit Dwi (Jurnal Biologi Tropis, 2024)
Indonesia is in fourth place with the highest prevalence of stunting in the Southeast Asia region. This study aims to determine the relationship between breastfeeding and the incidence of stunting. stunting. The method used is Observational Analytics with a cross sectional study design. Next, analyze the data using the Chi-Square test via the SPSS application. The research results found a relationship between breastfeeding and the incidence of stunting, namely p = 0.000 < 0.005. Toddlers in the Tanrutedong Community Health Center working area, Sidrap Regency in 2023 who do not receive exclusive breastfeeding are more likely to experience stunting. Further research is needed regarding other variables related to the incidence of stunting among toddlers in the Tanrutedong Community Health Center working area, Sidrap Regency. The consequences of this exploration can be utilized as a kind of perspective for completing routine assessments of youngsters who can possibly encounter hindering.